Relation to knowledge and written language in 5th and 9th grade students in two public institutions in Valle del Cauca, Colombia (Praxis Educativa, 2016)
The purpose of this research was to determine the relation to knowledge in its epistemic and affective dimensions that fifth and ninth grade basic education students established with the written language. This was an exploratory study, with a hermeneutic approach. The participants in this study were 105 fifth and ninth grade students of two public schools in Colombia. The results showed that most students had a weak epistemic and affective relation with written language. In the epistemic relation to knowledge, students made few evocations of intellectual learning related to writing; and showed difficulties in the domain of writing: errors in punctuation, spelling, sentence construction and structuring of ideas. In the affective relation to knowledge, students made few references related to the meaning and value of writing for their intellectual and personal development. These findings highlight the need to promote pedagogical strategies for teaching and learning writing that focus on students, their expectations and their network of relations to knowledge and learning.
Keywords: relation to knowledge; writing; espistemic relation; affective relation; basic education students.